2008
DOI: 10.1016/j.neuroscience.2007.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Forebrain circuitry involved in effort-related choice: Injections of the GABAA agonist muscimol into ventral pallidum alter response allocation in food-seeking behavior

Abstract: Organisms often make effort-related choices based upon assessments of motivational value and work requirements. Nucleus accumbens dopamine is a critical component of the brain circuitry regulating work output in reinforcement-seeking behavior. Rats with accumbens dopamine depletions reallocate their instrumental behavior away from food-reinforced tasks that have high response requirements, and instead they select a less-effortful type of food-seeking behavior. The ventral pallidum is a brain area that receives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 68 publications
(106 reference statements)
3
76
0
Order By: Relevance
“…This projection is GABAergic, and recent evidence indicates that extracellular levels of GABA, as measured by microdialysis, were increased by local accumbens core injections of either the adenosine A 2A agonist CGS 21680 [121] or the DA D 2 antagonist eticlopride (FIGURE 4) at doses that also produce the shift from lever pressing to chow intake in rats responding on the operant concurrent choice task. Consistent with this observation, it was reported that injections of the GABA A agonist, muscimol, directly into the ventral pallidum also decreased lever pressing and increased chow intake [132], while injections of muscimol into a control site dorsal to the ventral pallidum were ineffective. Moreover, injections of the adenosine A 2A agonist CGS 21680 into nucleus accumbens on one side of the brain, combined with muscimol injected into the ventral pallidum on the contralateral side, reduced lever pressing in rats responding on a VI 60 s schedule that had an additional work requirement (FR10) attached [121].…”
Section: Forebrain Circuits and Neurotransmitter Interactions Regulatinsupporting
confidence: 65%
See 1 more Smart Citation
“…This projection is GABAergic, and recent evidence indicates that extracellular levels of GABA, as measured by microdialysis, were increased by local accumbens core injections of either the adenosine A 2A agonist CGS 21680 [121] or the DA D 2 antagonist eticlopride (FIGURE 4) at doses that also produce the shift from lever pressing to chow intake in rats responding on the operant concurrent choice task. Consistent with this observation, it was reported that injections of the GABA A agonist, muscimol, directly into the ventral pallidum also decreased lever pressing and increased chow intake [132], while injections of muscimol into a control site dorsal to the ventral pallidum were ineffective. Moreover, injections of the adenosine A 2A agonist CGS 21680 into nucleus accumbens on one side of the brain, combined with muscimol injected into the ventral pallidum on the contralateral side, reduced lever pressing in rats responding on a VI 60 s schedule that had an additional work requirement (FR10) attached [121].…”
Section: Forebrain Circuits and Neurotransmitter Interactions Regulatinsupporting
confidence: 65%
“…Another part of this circuitry appears to be the ventral striatopallidal pathway. Neurons originating in nucleus accumbens core areas that have been implicated in effort-related processes project to the lateral ventral pallidum [121,132]. The cell bodies of many of these neurons also contain adenosine A 2A receptors [121].…”
Section: Forebrain Circuits and Neurotransmitter Interactions Regulatinmentioning
confidence: 99%
“…Several lines of evidence indicate that, in addition to nucleus accumbens DA, other brain areas and transmitters are involved in effort-related processes, including prefrontal cortex, amygdala, and ventral pallidum (Walton et al 2002(Walton et al , 2003Schweimer et al 2005;Schweimer and Hauber 2006;Floresco and Ghods-Sharifi 2007;Farrar et al 2008). Recent studies also have highlighted the involvement of the purine nucleoside adenosine in this type of function .…”
Section: Introductionmentioning
confidence: 99%
“…GABA (γ-aminobutyric acid) has been proposed to play a key role in the regulation of food intake and body weight 1 . Psychological factors, genetic predisposition and eating habits can increase body weight which may lead to obesity 2 .…”
Section: Introductionmentioning
confidence: 99%
“…GABA (γ-aminobutyric acid) a inhibitory neurotransmitter in the mammalian brain mainly present in the arcuate nucleus had been proposed to play a key role in the food preferences of selecting the type, quantity and quality of food by regulating the transmission of signals between neurons in brain circuits 12 . Additionally, the GABA a inhibitory neurotransmitter mainly involved in eating behaviour in experiments using rodent models and GABA receptor agonists and antagonists 13 .…”
Section: Introductionmentioning
confidence: 99%